1988
DOI: 10.1136/bjo.72.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Ocular and cardiovascular response to topical carteolol 2% and timolol 0.5% in healthy volunteers.

Abstract: SUMMARY Ocular and cardiovascular effects of carteolol 2%, timolol 0O5%, and dummy eyedrops have been measured in a single dose double-blind crossover study in six healthy volunteers. Both drugs lowered intraocular pressure and reduced exercise-induced tachycardia. Neither produced a significant change in resting heart rate or blood pressure. The two agents appear comparable as regards ocular hypotensive and cardiovascular effects.Topical beta adrenoceptor blocking drugs (beta blockers) are now the first line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 6 publications
(1 reference statement)
0
14
0
Order By: Relevance
“…Small case series evaluating topical timolol usually involving young healthy volunteers have variably demonstrated changes in blood pressure and heart rate, which have been considered clinically insignificant. [259][260][261] However, several case series and case reports with topical β-blockers, primarily timolol, have demonstrated clinically significant issues in patients with HF, including arrhythmias such as bradycardia, myocardial ischemia, hypotension, and pulmonary edema. 262,263 In 2 HF patients, topical timolol administration led to an exacerbation of symptoms of HF.…”
Section: β-Blockersmentioning
confidence: 99%
“…Small case series evaluating topical timolol usually involving young healthy volunteers have variably demonstrated changes in blood pressure and heart rate, which have been considered clinically insignificant. [259][260][261] However, several case series and case reports with topical β-blockers, primarily timolol, have demonstrated clinically significant issues in patients with HF, including arrhythmias such as bradycardia, myocardial ischemia, hypotension, and pulmonary edema. 262,263 In 2 HF patients, topical timolol administration led to an exacerbation of symptoms of HF.…”
Section: β-Blockersmentioning
confidence: 99%
“…Previous studies by ourselves and others have shown that such drugs, though applied to the eye in small quantities, are absorbed into the general circulation sufficiently to produce effects elsewhere in the body (Alvan et al, 1980). As a result, the cardiac response to exercise, for example, may be impaired (Smith et al, 1979;Brazier & Smith, 1988). In clinical practice resultant side-effects may occur in susceptible (particularly elderly) subjects; bradycardia, heart failure, hypotension, bronchoconstriction and pain in the legs on exertion have frequently been reported (Buskirk, 1980;Buskirk & Fraunfelder, 1981;Nelson et al, 1986 This paper reports a comparative healthy volunteer study of intraocular pressure and cardiovascular effects of timolol and the more recently introduced 3-adrenoceptor blocker metipranolol to find out whether the newer drug offers the advantage sought.…”
mentioning
confidence: 99%
“…-A further double-blind crossover study demonstrated comparable decreases in mean lOP of 2.2mm Hg and 2.3mm Hg, respectively, following administration of 2 drops of carteolol 2% or timolol 0.5% in 6 volunteers, significantly greater reductions than achieved with placebo (Brazier & Smith 1988). -A further double-blind crossover study demonstrated comparable decreases in mean lOP of 2.2mm Hg and 2.3mm Hg, respectively, following administration of 2 drops of carteolol 2% or timolol 0.5% in 6 volunteers, significantly greater reductions than achieved with placebo (Brazier & Smith 1988).…”
Section: Studies In Healthy Volunteersmentioning
confidence: 85%
“…Mean lOP also decreased by approximately 14 to 21% in the untreated eyes of healthy volunteers (Brazier & Smith 1988;Negishi et al 1981), suggesting a crossover effect resulting from systemic absorption of carteolol (see also section 1.3). However, placebo administration also caused a 4 to 11 % decrease in mean lOP in untreated eyes.…”
Section: Studies In Healthy Volunteersmentioning
confidence: 96%